Analysis of the Effectiveness of Stress Management Training for Nurses in Emergency Units - Sari, Wike Hariani (International Journal on Health and Medical Sciences, 2024)
Nurses working in emergency units are frequently exposed to high levels of stress due to the demanding nature of their roles. This study investigates the effectiveness of a stress management training program designed to alleviate stress, improve job satisfaction, and reduce burnout among emergency unit nurses. A mixed-methods approach was employed, combining quantitative and qualitative data. Participants included registered nurses from a single healthcare facility. The training program, delivered over six weeks, incorporated cognitive-behavioral techniques, mindfulness practices, and relaxation exercises. Stress levels, job satisfaction, and burnout were measured using the Perceived Stress Scale (PSS), the State-Trait Anxiety Inventory (STAI), the Job Satisfaction Survey (JSS), and the Maslach Burnout Inventory (MBI). Qualitative insights were gathered through semi-structured interviews. The training program led to a significant reduction in perceived stress and anxiety, with average decreases of 25% in PSS scores and notable improvements in STAI scores. Job satisfaction increased by 18%, and burnout levels decreased, with reductions of 20% in emotional exhaustion and 15% in depersonalization. The program also contributed to a 10% reduction in absenteeism and a 12% decrease in turnover intentions. Qualitative feedback highlighted enhanced coping strategies, improved emotional resilience, and better team dynamics.